Decision No. 109/2014 on amending some provisions of the decision of the authority's board of directors No. 72/2013 regarding the regulatory and supervisory controls governing factoring activity / Egyptian financial supervisory authority (EFSA) ; translated by The middle east library for economic services. - Egyptian financial supervisory authority (EFSA); The middle east library for economic services, translator. (2025)
Serial No. 70/2014